Using nonpneumatic anti-shock garment for postpartum hemorrhage management and referral at the public health facilities: A pilot study in two districts of Bihar - Jyoti Sharma; Preeti Negandhi; Ankan Mukherjee Das; Ghanashyam Sethy; Sutapa B Neogi (Wolters Kluwer Medknow Publications, 2016)
Background: Nonpneumatic anti-shock garment (NASG) is a first-aid device that can save lives of women experiencing postpartum hemorrhage (PPH). Objective: The aim was to explore the feasibility of implementation of NASG intervention at select public health primary care facilities in two high priority districts of Bihar. Methods: Qualitative design was used to document the NASG implementation process. In-depth interviews were conducted with health-care providers in November-December 2015. These healthcare providers were chosen purposively based on their involvement in the use of NASG. The implementation process of NASG, process of training for its use, challenges faced during the rollout of implementation and the recommendations for improving the implementation were explored. Results: Initially, a baseline study was conducted to assess the knowledge and skills of health-care providers regarding diagnosis and management of PPH. Implementation consisted of orientation and training of service providers on the identification of PPH cases and usage of the NASG garment during referrals. The interviews with stakeholders reflected that even after training and appropriate introduction of the practice of using the NASG bag, the initiative did not make a difference in ameliorating the situation of PPH management in the health facilities over 6 months. Conclusion: This study provides lessons for implementation and scaling up of NASG in public health systems, not only in Bihar but also other similar settings. It also calls for robust implementation research studies to generate evidence on the use of NASG at the primary health-care facilities as an intervention in program settings.